Non-optic glioma in adults and children with neurofibromatosis 1. Issue 1 (December 2017) - Sellmer, Laura; Farschtschi, Said; Marangoni, Marco; Heran, Manraj; Birch, Patricia; Wenzel, Ralph; Friedman, Jan; Mautner, Victor-Felix
Abstract Background Non-optic gliomas occur in 5% of children with NF1, but little is known about these tumours in adults. We aimed to investigate progression, spontaneous regression and the natural history of non-optic gliomas in adults and compare these findings to the results found in children. Results One thousand seven hundred twenty-two brain MRI scans of 562 unselected individuals with NF1 were collected at the NF outpatient department of the University Hospital Hamburg-Eppendorf between 2003 and 2015. The number of scans per patient ranged from one to 12; patients were followed for a median of 3.7 years. We identified 24 patients (4.3%) with non-optic gliomas. Median age at first scan with glioma was 21.2 years, much higher than in previous publications. Only seven of the 24 non-optic glioma patients were symptomatic. Five of 24 patients had multiple non-optic gliomas. Four individuals developed a new tumour, and 4 cases showed progression. The risk of new tumour development was 0.19% (95% confidence interval 0.06% to 0.52%) per patient year of follow-up for patients over 10 years. The rate of progressing non-optic gliomas per patient year of follow-up in the first 5 years after tumour diagnosis was 4.7% (95% confidence interval 1.5% to 12%). Conclusions Non-optic gliomas are twice as common in an unselected cohort of NF1 patients as previously reported. This is likely due to increased frequency of diagnosis of asymptomatic tumours when routine MRIs are performed and a higher prevalence in older individuals.